Improving Forensic Pathologic Investigation of Sudden Death in the Young: Tools, Guidance, and Methods of Cardiovascular Dissection from the Sudden Death in the Young Case Registry. Issue 2 (June 2018) - Gulino, Sam P.; Burns, Kristin; Gunther, Wendy M.; MacLeod, Heather
The Sudden Death in the Young (SDY) Case Registry, a prospective, population-based registry active in ten states, has developed tools to aid pathologists and death investigators in the evaluation and autopsy of unexplained, natural sudden deaths in the pediatric population. The tools were developed by a team of experts representing forensic pathology; pediatric-, cardiac-, and neuropathology; cardiology; neurology/epileptology; pediatrics; genetic counseling; and public health. These tools focus on collecting data relevant to determination of cause of death with a focus on dissection of the cardiovascular system. The tools provide an objective checklist format for ease of use and data extraction. By sharing the tools here and highlighting the examination of the cardiovascular system, the SDY Case Registry encourages a standardized approach to death investigation, autopsy, and data collection for sudden, unexpected deaths in the young towards a goal of informing prevention efforts. Acad Forensic Pathol. 2018 8(2): 347-391